La gamificación como estrategia didáctica en el aprendizaje del aparato locomotor en los alumnos de sexto año de Educación General Básica en la escuela Manuelita Sáenz del cantón Guaranda en el año lectivo 2024-2025. - Berzoza Carrera, Marcos Joel (2025)
The present study analyzes gamification as a teaching strategy for learning the musculoskeletal system in sixth-year students of Basic General Education at the Manuelita Sáenz school, Guaranda, during the period 2024-2025. The main objective was to determine how gamification improves motivation and academic performance in this topic. The theoretical perspective was based on constructivism, the theory of meaningful learning and the self-determination model, highlighting the active role of the student in their education. The methodology used was a mixed approach, combining quantitative data collection through surveys and qualitative data collection through teacher interviews. The results revealed that the students showed limited knowledge about the musculoskeletal system, highlighting confusion in basic concepts such as the function of muscles and bones. However, the implementation of gamified activities improved students' understanding and motivation by presenting interactive dynamics such as anatomical puzzles and simulations. In conclusion, gamification not only facilitated the acquisition of knowledge about the musculoskeletal system, but also promoted social and cognitive skills, recommending its integration into innovative educational methodologies for meaningful and motivating learning.